Nrf2-related gene expression and exposure to traffic-related air pollution in elderly subjects with cardiovascular disease: An exploratory panel study - Wittkopp, Sharine; Staimer, Norbert; Tjoa, Thomas; Stinchcombe, Timothy; Daher, Nancy; Schauer, James J; Shafer, Martin M; Sioutas, Constantinos; Gillen, Daniel L; Delfino, Ralph J (Journal of exposure science & environmental epidemiology, 2016)
Gene expression changes are linked to air pollutant exposures in in vitro and animal experiments. However, limited data are available on how these outcomes relate to ambient air pollutant exposures in humans. We performed an exploratory analysis testing whether gene expression levels were associated with air pollution exposures in a Los Angeles area cohort of elderly subjects with coronary artery disease. Candidate genes (35) were selected from published studies of gene expression-pollutant associations. Expression levels were measured weekly in 43 subjects (≤12 weeks) using quantitative PCR. Exposures included gaseous pollutants O 3 , nitrogen oxides (NO x ), and CO; particulate matter (PM) pollutants elemental and black carbon (EC, BC); and size-fractionated PM mass. We measured organic compounds from PM filter extracts, including polycyclic aromatic hydrocarbons (PAHs), and determined the in vitro oxidative potential of particle extracts. Associations between exposures and gene expression levels were analyzed using mixed-effects regression models. We found positive associations of traffic-related pollutants (EC, BC, primary organic carbon, PM 0.25-2.5 PAH and/or PM 0.25 PAH, and NO x ) with NFE2L2 , Nrf2-mediated genes ( HMOX1 , NQO1 , and SOD2 ), CYP1B1 , IL1B , and SELP . Findings suggest that NFE2L2 gene expression links associations of traffic-related air pollution with phase I and II enzyme genes at the promoter transcription level.